Bone and joint infection. (November 2017) - Bejon, Philip; Robinson, Esther
Abstract: Bone and joint infections are serious. They can be life-threatening or, more commonly, associated with long-term disability and reduced quality of life. The spectrum of disease has changed over time, and the proportion of iatrogenic disease caused by infected prosthetic joints is increasing annually. Osteomyelitis results when bacteria colonize bone, usually a sterile tissue, via direct inoculation from trauma or operation, haematogenous seeding from bloodstream infection or contiguous spread from another infected site. The pathophysiology of biofilm formation leads to a chronic infection that is not readily accessible to either host immunity or antibiotics. Presentation is with pain, swelling, lack of mobility and systemic symptoms. Diagnosis requires clinical symptoms, appropriate radiological imaging and microbiological sampling. Early or very limited osteomyelitis may be managed with antibiotics alone, but surgical debridement is key for many infections. Therapy should be undertaken by multidisciplinary teams including infection specialists, surgeons, radiologists and other clinical professionals.